DIVERSITY AND PHENETIC STUDY ON SYCONIUM OF FICUS L. (MORACEAE) FROM KERALA, INDIA REVEALING NATURAL CLASSIFICATION ALONG WITH AN IDENTIFICATION KEY - Sreehari S Nair; K.H. Amitha Bachan; P.J. Ebin (REINWARDTIA, 2021)
NAIR, S. S., BACHAN, K. H. A.  &  EBIN, P. J.  2021. Diversity and phenetic study on syconium of Ficus L. (Moraceae) from Kerala, India revealing natural classification along  with an identification key. Reinwardtia  20(1): 27–36. — Ficus L. commonly called ‘figs’ is one of the most complex genera among the angiosperms with its specialised inflorescence called syconium that looks like a fruit. Syconium of 33 species of  Ficus reported from Kerala were observed here to develop a novel key, solely based on syconium morphology. Numerical taxonomic methodology  for syconium  morphological characters  were standardised, considering 22 characters with 104 character states and analysed using similarity clustering. The floral features of the genus are very much complex and all the existing keys for the species identification relays on both vegetative as well as floral features. Hence, the present key will be practical  in  use  when  syconium  is  the  only  available  part.  The  numerical  analysis  of  the  syconium  features  well clustered and separated the trees with cauliflorous inflorescence, hemi epiphytic -epiphytic life forms and independent trees similar to the natural classification of the figs as  “Atthi, Itthi and Aal”, indicating that phenetic analysis using the syconium  characters  alone  provided  a  grouping  similar  to  the  natural  grouping  based  on  the  habit.  Preliminary phylogenetic analysis of figs also provided a similar clustering. This gives an insight into the fact that the separation of figs into these natural groups is reflecting phylogenetic trait. Detailed studies including more morphological traits and molecular analysis could establish the phylogenetic relation of figs in relation to the evolutionary history of climate and vegetation.